黄河流域文明的发祥与发展 - 严文明 (华夏考古, 1997)
The civilization of the Yellow River valley was developed on the basis of millet-farming agriculture. The society in this area began to break up and went to civilization at about 3500 B. C. From 3000B. C.to 2100B. C. of the Longshan Times,many walled towns or cities emerged and thus the dawn of ancient Chinese civilization came into being. The following Erlitou Culture may have been the culture of the Xia people during the Xia Dynasty. The Xia State became the largest one among states in the Yellow River valley after Shaokang's rejuvenation. The Shang and Zhou expanded their forces into the Yangtze River valley and the Yanshan Mountain and the Liaohe River valley. Once ancient Chinese civilization reached its prosperity, the central place of the Yellow River valley established.
Keywords: 黄河流域; 龙山时代; 二里头文化; 龙山城址; 黄河中游; 二里头遗址; 长江流域; 禅让制度; 岳石文化; 酋邦